UPAYA MENINGKATKAN MINAT BELAJAR SISWA MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING KELAS XI PADA MATERI TRIGONOMETRI - Abdul Sofyan; M. Imamuddin; Elva Ramli (KOLONI, 2022)
The background of this research is the students' lack of interest in learning mathematics, especially in trigonometry material. The research objective was to determine the increase in students' interest in learning mathematics through discovery learning models on Trigonometry material. The research method used is an experimental method by administering pre-test and post-test questionnaires. The research sample consisted of 20 students of class XI IPA 3 at SMA N 1 JUNJUNG SIRIH. The data analysis technique uses the r-test. Based on the results of the research, it shows that the natural discovery learning model of learning mathematics brings an increase in students' interest in learning, especially in Trigonometry material. Keywords: mathematics, interest in learning, discovery learning